The Effect of Story-Based Learning Media on the Formation of Honest Character in Children at SDN Geredug 1 - Nandang Kusmana; Wila Widia; Susilawati; Lita Arofatusolihah; Aini; Rifki Gozali (Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This study aimed to evaluate the effectiveness of storybased learning tools in promoting positive character development among elementary school students Honesty is a crucial component that molds human character. This study uses a qualitative descriptive methodology to describe the process of establishing the character value of honesty. The study's subjects were eighteen first-graders from Geredug 1 Public Elementary School in Bojong District, Pandeglang Regency. Data was gathered during the learning process through observation, interviews, and documentation. Stories were the main means of teaching the principle of honesty since they may simultaneously effect students' cognitive, emotive, and psychomotor abilities. The findings demonstrated that telling stories to kids can improve their comprehension and knowledge of the need of honesty. Pupils were more inclined to speak truthfully, own up to their mistakes, and exhibit consistent behavior in both words and deeds. As a result, stories can be utilized as an educational substitute to enhance character education in primary schools, especially when it comes to teaching kids the need of honesty at a young age.